Evaluasi Sistem Informasi Manajemen Pendidikan Pada Gugus I Kairatu Barat - Irawan Sialimbona; R. Kempa; A. Sahalessy; Sumarni Rumfot (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
The rapid advancement of information technology in various sectors is inevitable. Information technology that is increasingly sophisticated on the one hand facilitates human work and at the other end increasingly requires humans to be able to operate it. In that context, improvement in the field of information technology is a very urgent need. Schools as educational institutions cannot escape the advancement of information technology. Schools are required to implement a good management information system. This is done so that schools can improve efficiency and effectiveness in managing school management. This research aims to find out (1). The extent of the implementation of the Education management information system in cluster 1 West Kairatu. (2). What factors are supporting and inhibiting the implementation of Academic SIMDIK in cluster 1 West Kairatu. This study used descriptive qualitative research, using observation, interviews and documentation, as data collection techniques. This research was conducted in three schools in cluster 1 west Kairatu. Based on the research, the results obtained are: (1) Input Aspect: The results of the initial study of the implementation of Academic SIMDIK, the Input dimension found that input data such as: Data based students, educators and education personnel, lesson plan documents, curriculum and so on have been well organized. The results of observations of dimension (2) process: it was found that curriculum and learning management, teacher assignments, scheduling, teaching units, teaching plans, subject management, student attendance in PBM, question bank data processing, management of test scores, were quite good, but student case data was not well organized. The results of the observation of dimension (3) Product: it was found that the management of student academic grades, academic achievements and student study reports were well organized. Supporting factors, the principal is proficient in using IT, administrative management is quite good. While inhibiting factors There are still principals, teachers who cannot use IT properly, especially senior teachers who are about to retire, inadequate computer equipment, internet networks and electricity that are less supportive, especially when sending data.